Remembering the dead : a Penny Brannigan mystery - Duncan, Elizabeth J (Duncan, Elizabeth J. Penny Brannigan mystery., 2019)
Artist and spa owner Penny Brannigan has been asked to organize a formal dinner to mark the centenary of the armistice that ended World War One. After dinner, the guests adjourn to the library for a private exhibition of the Black Chair, a precious piece of Welsh literary history awarded in 1917 to poet Hedd Wyn. But to the guests' shock, the newly restored bardic chair is missing. And then Penny discovers the rain-soaked body of a waiter. When Penny learns that the victim was the nephew of one of her employees, she is determined to find the killer. Meanwhile, the local police search for the Black Chair. The Prince of Wales is due to open an exhibit featuring the chair in three weeks, so time is not on their side. A visit to a nursing home to consult an ex-thief convinces Penny that the theft of the Black Chair and the waiter's murder are connected. She rushes to Dublin to consult a disagreeable antiquarian, who might know more than he lets on, and during the course of her investigation confronts a gaggle of suspicious travelers and an eccentric herbalist who seems to have something to hide. Can Penny find the chair and the culprit before she is laid to rest in the green grass of Wales?